ANALISIS PENERAPAN TOTAL PRODUCTIVE MAINTENANCE (TPM) MELALUI METODE OVERALL EQUIPMENT EFFECTIVENESS (OEE) PADA MESIN PACKER DI PABRIK SEMEN PT. XYZ: Array - Pratama, M. Agung; Kurniawan, Fadly Ahmad; Irwan, Ade (JiTEKH, 2020)
XYZ is a manufacturing company engaged in the production of red and white cement. PCC cement packaging uses the main machine, namely the Rotary Packer machine, the packaging depends on consumer demand. If consumer demand continues to increase, the packaging process will take place continuously without stopping, and on the contrary, if consumer demand decreases slightly, the packaging process will also take place less. The high downtime of the Packer 1 machine causes production targets to be achieved, delays in the distribution process, and non-productive activities for employees. Based on these problems, the calculation of the effectiveness value on the Packer 1 machine using the Overall Equipment Effectiveness (OEE) method. Which aims to determine the value of OEE (Overall Equipment Effectiveness) of the Packer 1 machine, to determine the comparison of the OEE value of the Packer 1 machine with international OEE values, and to determine the priority factors for repair and the root causes of problems and solutions. Based on the results of data processing, it can be concluded that the Packer 1 machine OEE value is 16.98% which is obtained from the Availability Ratio value of 49.48%, the Performance Efficiency Ratio of 30.04 and the Rate of Quality product of 100%.